1983
DOI: 10.1084/jem.158.3.703
|View full text |Cite
|
Sign up to set email alerts
|

Activation of antigen-specific suppressor T cells by B cells from mice immunized with type III pneumococcal polysaccharide.

Abstract: The transfer of B lymphocytes from mice immunized with type III pneumococcal polysaccharide (SSS-III) results in antigen-specific suppression of the antibody response of recipients immunized with SSS-III. Such suppression shares many features associated with low-dose paralysis, a phenomenon mediated by suppressor T cells; it reaches maximal levels 3 d after the transfer of viable or irradiated immune B cells and can be eliminated by the depletion of SSS-III-binding cells from spleen cell suspensions before tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
29
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…It has long been established in mice [1][2][3] that Ihc antibody response to T-cell independent type 2 (TI-2} antigens is determined by the activities of two functionally distinct types of regulatory T cells with opposing functions. On the one hand amplifier T cells have been delineated which can enhance an antibody response [I.…”
mentioning
confidence: 99%
“…It has long been established in mice [1][2][3] that Ihc antibody response to T-cell independent type 2 (TI-2} antigens is determined by the activities of two functionally distinct types of regulatory T cells with opposing functions. On the one hand amplifier T cells have been delineated which can enhance an antibody response [I.…”
mentioning
confidence: 99%
“…Pneumococcal capsuiar polysaecharide antigens are often employed in the study of the immune response against polysaccharides in animals as well as in humans [1,3,10]. In vitro studies have suggested that the B-cell response in humans-as in mice \2, 4,8,9]-is T-cell independent; it is, however, probably regulated by T cells [3,16,19,20].…”
mentioning
confidence: 99%
“…18], and Taylor et ut. [21] give evidence for the induction of anti-anti-SSSIII-specific suppressor cells as the result of immunization. In further experiments we have separated, with high performanee ion exehange…”
Section: Discussionmentioning
confidence: 93%